2020
DOI: 10.1002/jmv.25731
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history, potential intermediate animal host, and cross‐species analyses of SARS‐CoV‐2

Abstract: To investigate the evolutionary history of the recent outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in China, a total of 70 genomes of virus strains from China and elsewhere with sampling dates between 24 December 2019 and 3 February 2020 were analyzed. To explore the potential intermediate animal host of the SARS-CoV-2 virus, we reanalyzed virome data sets from pangolins and representative SARS-related coronaviruses isolates from bats, with particular attention paid to the spike gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
390
10
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 417 publications
(450 citation statements)
references
References 53 publications
(102 reference statements)
33
390
10
10
Order By: Relevance
“…Furthermore, the amino acid homologies of ORF1ab, N, S proteins of the two viruses are 98.55, 99.05 and 97.41% respectively. These results suggest the two viruses have a high genetic relationship, which is consistent with the results reported previously Li et al, 2020;Paraskevis et al, 2020;Zhou et al, 2020). Moreover, the N protein of SARS-CoV-2 and bat coronavirus RaTG13 had 4 different amino acids, which were 37S/P, 215G/S, 243G/S, and 267A/Q, respectively.…”
Section: To the Editorsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, the amino acid homologies of ORF1ab, N, S proteins of the two viruses are 98.55, 99.05 and 97.41% respectively. These results suggest the two viruses have a high genetic relationship, which is consistent with the results reported previously Li et al, 2020;Paraskevis et al, 2020;Zhou et al, 2020). Moreover, the N protein of SARS-CoV-2 and bat coronavirus RaTG13 had 4 different amino acids, which were 37S/P, 215G/S, 243G/S, and 267A/Q, respectively.…”
Section: To the Editorsupporting
confidence: 92%
“…: MN996532), with 96.2% nucleotide homology in the whole genome Zhou et al, 2020). Other groups suggest that pangolin, mink, snake, turtle may be potential intermediate hosts for the virus (Association, 2020;Guo et al, 2020;Ji et al, 2020;Lam et al, 2020;Li et al, 2020;Liu et al, 2020a;Liu et al, 2020b;Xiao et al, 2020;Zhang et al, 2020a;Zhang et al, 2020b), which still need more evidence to be confirmed.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…1 SARS-CoV-2 is also related to SARS-CoV and Middle East respiratory syndrome coronavirus (MERS-CoV), which cause severe disease that is associated with high mortality rates. 2,3 Coronaviruses originate in bats but are zoonotic and can circulate in a number of mammals and birds. 1 SARS-CoV emerged into the human population because of the exotic food trade in China, which allowed for a transmission event between a civet cat and a human.…”
Section: Introductionmentioning
confidence: 99%